2022
DOI: 10.1024/2673-8627/a000019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rejection Sensitivity on Fear of Intimacy in Emerging Adulthood

Abstract: Abstract. Background: This research examined fear of intimacy during emerging adulthood. We attempted to determine whether rejection sensitivity has any effect on fear of intimacy through the mediational effect of interpersonal anxiety. We also assumed that remembered parental acceptance can have a buffering effect on the above relationships. Methods: The sample was composed of 679 (280 male and 399 female) university students. Data collection was accomplished through the use of self-report questionnaires, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
3
0
1
Order By: Relevance
“…Regardless of the previous limitation pertaining to the analysis, future studies on fear of intimacy might need to consider other factors. For instance, parental rejection (Rohner et al, 2019), rejection sensitivity (Giovazolias & Paschalidi, 2022), and maladaptive cognitive schemata (Obeid et al, 2019) were recently reported to be associated with fear of intimacy. It would be interesting to see whether these studies could be replicated in Indonesian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the previous limitation pertaining to the analysis, future studies on fear of intimacy might need to consider other factors. For instance, parental rejection (Rohner et al, 2019), rejection sensitivity (Giovazolias & Paschalidi, 2022), and maladaptive cognitive schemata (Obeid et al, 2019) were recently reported to be associated with fear of intimacy. It would be interesting to see whether these studies could be replicated in Indonesian population.…”
Section: Discussionmentioning
confidence: 99%
“…Terlepas dari kelemahan analisis yang disebutkan sebelumnya, faktor lain mungkin perlu dipertimbangkan dalam kajian ketakutan akan intimasi. Misalnya, penolakan orang tua (Rohner dkk., 2019), sensitivitas terhadap penolakan (Giovazolias & Paschalidi, 2022), dan skema kognitif yang maladaptif (Obeid dkk., 2019) baru-baru ini ditemukan berkaitan dengan ketakutan akan intimasi. Faktor-faktor ini tentu saja menarik untuk dikaji dalam konteks Indonesia.…”
Section: I S K U S Iunclassified
“…However, another line of research has emphasized the socially constructed relational direction of female identity, assuming that high rejection sensitive young females will be more likely to experience interpersonal distress such as a higher fear of intimacy compared to males [44]. Indeed, it has been supported that females appear to be more sensitive to social stimuli than males and are more likely to harm their relationships as a response to interpersonal stressful incidents [45] and that late female adolescents [46] as well as young female adults [39] report significantly greater RS and interpersonal anxiety than males. Other research has shown that male adolescents are more sensitive to signs of rejection when their social status is threatened [9], and this sensitivity combined with relatively underdeveloped emotional-supportive relationships may explain the higher levels of RS in males [47].…”
Section: Gender Differencesmentioning
confidence: 99%
“…Rejection sensitivity can be conceptualized as a defensive motivational system that may be rooted in early prolonged and repeated experiences of rejection by significant others (Pietrzak et al, 2005). It also predicts interpersonal anxiety and fear of intimacy in young adults (Giovazolias & Paschalidi, 2022). Although rejection sensitivity is used in some works interchangeably with interpersonal sensitivity (e.g., Harb et al, 2002), we regard these constructs as separate, which is corroborated by moderate correlations between rejection sensitivity and interpersonal sensitivity scales yielded in a study of gay men in the USA (Pachankis et al, 2008).…”
mentioning
confidence: 99%